(untitled) (Perioperaciina Medicina, 2026)
Abstract: A retrospective analysis was performed on 89 cases of endoscopic ultrasound-guided fine-needle aspiration biopsy (EUS-FNA) from tumors of the hepato-pancreato-biliary system (n=46), gastrointestinal (GI) wall lesions (n=33), and extra-organ localizations (n=10). Morphological verification of the diagnosis was successful in 33 patients (71.7 %) of the first group, in 28 patients (84.8 %) of the second group, and in 7 patients (70.0 %) of the third group. Non-informative results in 21 cases (23.6 %) across all groups were due to insufficient quantity or poor quality of material caused by inflammatory, fibrotic, or necrotic changes, as well as contamination of aspirates with a significant number of blood elements and adjacent tissues. According to the literature, complications such as post-procedural pancreatitis and bleeding occur in 1.0 %–5.0 % of EUS-FNA cases, which is significantly lower than with percutaneous core-needle biopsy (2.0 %–10.0 %). EUS-FNA is a minimally invasive and highly informative diagnostic method, making it the method of choice for morphological diagnosis of neoplasms in the specified localizations. Objective: To determine the sensitivity of EUS-FNA in neoplasms of the hepato-pancreato-biliary system, gastrointestinal wall, and extra-organ tumors; to evaluate the results of cytological and histological verification of the diagnosis based on EUS-FNA material. Methods: Between August 2023 and April 2025, 89 patients with suspected neoplasms of the hepato-pancreato-biliary system (n=46), gastrointestinal wall lesions (n=33), and extra-organ localizations (n=10) underwent EUS-FNA at the National Cancer Institute of Ukraine. All patients underwent preliminary endoscopic imaging, followed by 3–5 passes (≈15 to-and-fro movements) under EUS guidance using 19G or 22G needles, with needle choice depending on lesion depth, vascularity, and structure. Samples were fixed in 10 % formalin or 70 % ethanol and sent for cytological and histological examination. Inadequate samples (by quantity or quality) underwent repeat biopsy in 17 (19.1 %) cases. Sample adequacy was assessed by the volume of cellular and tissue components. Sensitivity was determined by verification results and statistical comparison of groups using Pearson’s χ² test and the Mann–Whitney U test. Results: In the hepato-pancreato-biliary group (n=46), cytological verification was achieved in 20 (43.5 %) cases, histological in 15 (32.6 %). Repeat biopsy in 6 (13.0 %) cases was successful in 4 (8.7 %), increasing the overall informativeness by 5.1 %, resulting in full diagnosis in 33 (71.7 %) patients. Among 33 patients with GI wall tumors, cytology was informative in 19 (57.6 %) cases, histology in 13 (39.4 %). Repeat biopsy in 8 (24.2 %) cases was successful in 5 (15.2 %), increasing the rate by 22.3 %, for a total of 28 (84.8 %) complete verifications. In the extra-organ group (n=10), cytology was informative in 3 (30.0 %) cases, histology in 3 (30.0 %). Repeat biopsy in 3 (30.0 %) cases was successful in 2 (20.0 %), increasing the rate by 4.0 %, for a total of 7 (70.0 %) full verifications. The morphological spectrum of detected pathology included adenocarcinoma in 42 (47.2 %) cases, squamous cell carcinoma in 11 (12.3 %), and gastrointestinal stromal tumor (GIST) in 11 (12.3 %). In less than one-fourth of cases (21; 23.6 %), the material was non-informative due to cystic, necrotic, or fibrotic changes or the presence of adjacent tissues. The obtained data indicate high sensitivity of EUS-FNA, ranging from 70.0 % to 84.8 % depending on tumor localization. Conclusions: EUS-FNA is an effective method for verification of gastrointestinal tumors and, compared to classical puncture techniques, has a lower complication rate for post-procedural pancreatitis and bleeding. Optimization of technical aspects of the procedure improved the diagnostic efficiency and accuracy of morphological verification in patients with hepato-pancreato-biliary, gastrointestinal wall, and extra-organ neoplasms